Misteri La Ba’sa Bihi: Mengungkap Problem Subyektifitas dalam Jarh Wa Ta’dil - Alipullah, Randi; Firdausy, Hilmy (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
As one of the branches of hadith science, the issues surrounding jarh wa al-ta’dil certainly cannot be separated from the development of hadith itself. As we know that the demands of the times from time to time make the needs of society increasingly varied, not least in the field of hadith. The senior critics because of their mission to save the hadith from various forms of forgery tend to be harsh and strict in their assessment of the hadith narrators (tasyaddud) or at least moderate (i’tidal). Whereas the latter scholars since they aim to help the traditions that have been marginalized or overlooked tend to have a lenient attitude (tasahul). This is certainly in the subjective realm, so that a single sigat used to assess a narrator cannot be evenly distributed because of the different criteria set by each critic. One of the memorizations that is still a mystery and quite controversial is la ba‘sa bihi which when viewed from the meaning of the language alone tends to lead the reader to interpret it freely. To answer this problem, a method that is quite relevant and widely used by recent scholars is muqa>ran (comparative). With this method, it can be ascertained that la ba‘sa bihi is more inclined to the meaning of siqah or others. Keywords: Hadith critics; La ba‘sa bihi; Jarh wa ta’dil